PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR PERKEMBANGAN HEWAN MAHASISWA KELAS IVD PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP – UIR PEKANBARU TAHUN AJARAN 2013/2014 - SURYANTI ' ' (Biogenesis, 2015)
This study aims to determine the learning outcomes of students of the fifth semester of Biology Education Study class-UIR IVD FKIP Pekanbaru Academic Year 2013/2014 by using model Cooperative Integrated Reading and Composition. . Classroom action research was conducted in August and November 2013/2014. The subject is biology education students who are 40 people. Using descriptive analysis techniques. Improved cognitive value (Quiz) students from before PTK 69.92% of the first cycle of 79.52% increased 9.6%. while from cycle 1 to cycle II obtained is 76.78%, a decline of 2.7%. Psychomotor value (KI) in the first cycle of 85.07%, then the second cycle obtained 87.25%% increased only 2:18. In conclusion, an increase in student learning outcomes after the application of learning by problem though is not so high.Keywords: CIRC, Learning Outcomes, Animal Development